NEGATIVE ELECTRODE MATERIAL AND CURRENT COLLECTOR MATERIAL FOR Mg SECONDARY BATTERY, AND Mg SECONDARY BATTERY USING THE SAME

JP2024002369A5Active Publication Date: 2025-04-03NAT INST FOR MATERIALS SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022101515
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-06-24
Publication Date
2025-04-03
Estimated Expiration
2042-06-24

AI Technical Summary

Technical Problem

Existing secondary batteries face challenges in reducing weight by using lightweight materials as current collectors while maintaining excellent electrochemical properties and ensuring stable bonding with negative electrode materials.

Method used

A cladding material composed of an Mg layer made of Mg or Mg-based alloy and an Al layer made of Al or Al-based alloy, with controlled thickness, grain size, and minimal gaps, processed to introduce plastic strain for improved bonding and electrochemical performance.

Benefits of technology

The solution achieves lightweight secondary batteries with enhanced cycle characteristics, low overvoltage, and high current density, supporting efficient charge-discharge cycles and reducing the risk of short circuits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide a negative electrode material and a current collector material for a Mg secondary battery.SOLUTION: A cladding material consists of a Mg layer composed of Mg or a Mg-based alloy, and an Al layer composed of Al or an Al-based alloy, and consists of Mg-Ajmol%Xj (j=1, 2, ..., and n; n is a natural number of 1 or more), Xj targets an element solid-dissolved at 0.05 mol% or more with respect to Mg, Xj is composed of any one kind of element out of Al, Ag, Bi, Ca, Sn, Mn, Li, RE (rare earth), and Zn, a value of Aj is 0.02 mol% or more and 1 mol% or less, the Al-based alloy consists of Al-Bkmol%Yk (k=1, 2,..., and m; m is a natural number of 1 or more), Yk is composed of any one kind of element out of Si, Fe, Cu, Mn, Mg, Zn, Ti, Ag, Ga, and Li, a value of Bk is 0.02 mol% or more and 1 mol% or less, the Mg layer is a negative electrode material, and the Al layer is an Al current collector.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a negative electrode material and current collector for Mg secondary batteries using a clad material consisting of an Mg layer made of Mg or an Mg-based alloy having excellent electrochemical properties and an Al layer made of Al or an Al-based alloy, and to a Mg secondary battery using the same. [Background technology]

[0002] Power sources (batteries) are essential for mobile electronic devices such as smartphones and laptops. Due to their high electromotive force and high energy density, lithium secondary batteries are used in the majority of these devices. Meanwhile, magnesium (Mg) secondary batteries have been attracting attention in recent years. The main factor is the number of cations; whereas lithium ions are monovalent, magnesium ions are divalent ions, and theoretically, magnesium ions have twice the energy capacity of lithium secondary batteries. In addition, magnesium reserves are abundant in the earth, it has the second highest density of all practical metal elements after lithium, and Mg bulk has other advantages such as being extremely stable and easy to handle.

[0003] Normally, storage batteries such as secondary batteries are composed of a negative electrode material, a positive electrode active material, and an electrolyte. The inventors have focused on negative electrode materials and made the following proposal. Patent Document 1 discloses a negative electrode material that utilizes plastic processing methods such as rolling and is characterized by the segregation of added elements at grain boundaries. The amount of added elements is within the solid solubility range of each element, and the added element is one of the following elements that are solid soluble in Mg: Al, Ag, Bi, Ca, Sn, Mn, Li, RE (rare earth), and Zn.

[0004] The inventors also proposed in Non-Patent Document 1 that refining the crystal grain size of the Mg parent phase has the potential to improve electrochemical properties. Usually, the internal microstructure of metal materials created by rolling, extrusion, etc. changes significantly depending on the plastic processing conditions, including temperature and deformation amount. In particular, in bulk materials in which grain refinement is attempted, strain introduced during processing often remains in the parent phase. Therefore, Patent Document 2 investigates the relationship between residual dislocation density and voltage-current cycle characteristics, and discloses a Mg-based alloy negative electrode material with a small residual dislocation density in the Mg parent phase and excellent electrochemical properties.

[0005] The inventors have not only developed an Mg-based alloy negative electrode material in which the internal structure of the Mg matrix is ​​controlled based on metallurgy, but also disclosed in Patent Document 3 an Mg-based negative electrode material made of an Mg-based composite material containing one or more of carbon, carbide, nitride, and oxide in order to further improve electrochemical properties.

[0006] On the other hand, secondary batteries and other storage batteries require terminals to extract current from the positive and negative electrodes, and current collectors are used for these terminals. These current collectors are required to have excellent electronic conductivity, to exist stably within the storage battery, to be able to contract their volume within the battery, and to have adhesion to the positive and negative electrode materials.

[0007] Therefore, Patent Documents 4 and 5 disclose anode materials in which Mg is coated by plating on a current collector made of Cu, Al, stainless steel, Ni or a carbonaceous material. The thickness of Mg is preferably 1 μm to 20 μm, and the plating method is characterized by not being limited as long as it is a plating method that can form a plating layer with a homogeneous thin film structure. Patent Document 6 discloses a current collector made of carbon, carbon paper, carbon cloth, or precious metal mesh or foil, in which a paste material is deposited or heat-treated as necessary. Patent Documents 7 and 8 disclose secondary batteries in which the current collector is made of Cu, Ni, stainless steel, or Fe, and the bonding of the Mg anode material to the current collector is performed by compression bonding as an example.

[0008] However, from the viewpoint of reducing the weight of secondary batteries, it is desirable to use lightweight materials for the current collectors, and it is essential to simplify the process and increase the size of the materials.

[0009] On the other hand, Patent Document 9 discloses a manufacturing method in which workpieces are stacked and rolled to create a bulk body. The method targets metal materials such as stainless steel and Al alloys, and by increasing the strain introduced into the workpiece, good interface bonding and fine parent phase size (grain refinement) are achieved. However, the applications and use of these rolled materials are structural members that require strength and ductility, and it is important to ensure the thickness of the created material. For this reason, the method is characterized by stacking and rolling the workpieces many times. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] PCT / JP2021 / 4058 publication [Patent Document 2] Patent Application No. 2021-132315 [Patent Document 3] Patent Application No. 2021-85854 [Patent Document 4] JP 2012-531725 A [Patent Document 5] JP 2014-179336 A [Patent Document 6] JP 2013-8671 A [Patent Document 7] JP 2019-169467 A [Patent Document 8] JP 2019-192632 A [Patent Document 9] Patent No. 2961263 [Non-patent literature]

[0011] [Non-Patent Document 1] Bandai, Somekawa, ChemComm 56 (2020) 12122 Summary of the Invention [Problem to be solved by the invention]

[0012] The problem that the present invention aims to solve is to provide a negative electrode material and a current collector for Mg secondary batteries that can reduce the weight of secondary batteries by using a lightweight material as a current collector, and that can also meet the demand for larger battery materials from the standpoint of simplifying the manufacturing process and ensuring battery capacity. [Means for solving the problem]

[0013] [1] The negative electrode material and current collector for Mg secondary batteries of the present invention are clad materials consisting of an Mg layer made of Mg or an Mg-based alloy and an Al layer made of Al or an Al-based alloy, and the Mg-based alloy is Mg-A j mol%X j (j=1, 2, …, n; n is a natural number greater than or equal to 1), and X j X is for elements that are dissolved in Mg at 0.05 mol% or more. j = Consists of one of the following elements: Al, Ag, Bi, Ca, Sn, Mn, Li, RE (rare earth), and Zn. j The value of is 0.02 mol% or more and 1 mol% or less, The Al-based alloy is Al-B k mol%Y k (k=1, 2, …, m; m is a natural number equal to or greater than 1), and Y k = composed of one of the elements Si, Fe, Cu, Mn, Mg, Zn, Ti, Ag, Ga, and Li, and B k The value of is 0.02 mol % or more and 1 mol % or less, the Mg layer made of Mg or an Mg-based alloy is a negative electrode material, and the Al layer made of Al or an Al-based alloy is an Al current collector. Elements with a composition ratio of less than 0.02 mol% are considered to be unavoidable impurities.

[0014] [2] In the negative electrode material for Mg secondary batteries and the current collector material [1] of the present invention, preferably, the Mg layer has a thickness of less than 100 μm, and the Al layer has a thickness of less than 100 μm. [3] In the negative electrode material and current collector for Mg secondary batteries [1] or [2] of the present invention, preferably, the average crystal grain size of the Mg matrix of the Mg layer is 50 μm or less, and the average crystal grain size of the Al matrix of the Al layer is 50 μm or less. [4] In the negative electrode material and current collector for Mg secondary batteries according to the present invention [1] to [3], preferably, in a cross section observed with an optical microscope or a scanning electron microscope, there is a gap of less than 50% at the boundary between Al and Mg.

[0015] [5] In the negative electrode material and current collector for Mg secondary batteries according to the present invention [1] to [4], it is preferable that the negative electrode material and current collector exhibit a cycle characteristic of 20 or more cycles in a cycle measurement using a bipolar cell. [6] In the negative electrode material and current collector for Mg secondary batteries according to the present invention [1] to [5], it is preferable that the negative electrode material and current collector exhibit an overvoltage of 30 mV or less in an electrochemical deposition-dissolution test of Mg metal. [7] In the negative electrode material and current collector for Mg secondary batteries according to the present invention [1] to [6], preferably, in an electrochemical deposition and dissolution test of Mg metal, the electrochemical dissolution current is within ±10 mAcm when the electrode potential is ±0.5 V. -2 It is advisable to indicate the current density above.

[0016] [8] The method for producing the negative electrode material and current collector for Mg secondary batteries of the present invention is a method for producing the negative electrode material and current collector for Mg secondary batteries [1] to [7], in which an Mg layer composed of Mg or an Mg-based alloy and an Al layer composed of Al or an Al-based alloy are superimposed, and plastic strain is imparted by wrought processing at a temperature of 300°C or higher so that the true strain is 0.05 or more and less than 5.

[0017] [9] In the method for producing a negative electrode material and a current collector for a Mg secondary battery according to the present invention [8], the method for imparting plastic strain is preferably any one of extrusion, forging, rolling, drawing and twin-roll casting.

[0018]

[10] The Mg secondary battery of the present invention is composed of the negative electrode material and current collector for Mg secondary batteries described in any one of [1] to [7], an electrolyte, and a positive electrode. [Brief description of the drawings]

[0019] [Figure 1] 1 is an example of cross-sectional observation of a negative electrode material for a Mg secondary battery and a current collector according to Example 1, and shows images obtained by a scanning electron microscope. [Diagram 2] In the cross-sectional structure observation example of the negative electrode material for a Mg secondary battery and the current collector according to Example 1, an image obtained by an electron backscatter diffraction technique is shown as an IQ image. [Diagram 3] 1 shows an example of an electrochemical deposition / dissolution test of a negative electrode material and a current collector for a Mg secondary battery according to Example 1, and shows cycle voltage / current results. [Figure 4] 1 is an example of microstructure observation of the Mg alloy negative electrode material according to Example 2, and shows an image obtained by a scanning electron microscope. [Diagram 5] In the cross-sectional structure observation example of the negative electrode material for a Mg secondary battery and the current collector according to Example 2, an image obtained by an electron backscatter diffraction technique is shown as an IQ image. [Figure 6] FIG. 1 shows an example of an electrochemical deposition / dissolution test of a negative electrode material and a current collector for a Mg secondary battery according to Example 2, and shows cycle voltage / current results. [Figure 7] FIG. 1 is a schematic diagram showing a schematic configuration of a Mg secondary battery in which the negative electrode material for a Mg secondary battery and the current collector of the present invention are used. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] The negative electrode material and current collector for Mg secondary batteries of the present invention are constructed using a clad material consisting of an Mg layer made of Mg or an Mg-based alloy and an Al layer made of Al or an Al-based alloy. The Mg layer in this embodiment includes a pure Mg layer and an Mg alloy layer, and is used as the negative electrode material for Mg secondary batteries. The Mg-based alloy used for the Mg layer of the clad material is Mg-A j mol%X j (j=1, 2, …, n; n is a natural number greater than or equal to 1), and X j X is for elements that are dissolved in Mg at 0.05 mol% or more. j = Any one of the following elements: Al, Ag, Bi, Ca, Sn, Mn, Li, RE (rare earth), or Zn. Rare earth refers to the same group of elements such as Y (yttrium), Gd (gadolinium), Ce (cerium), and Sc (scandium). Here, n is 1 for a binary alloy, and 2 for a ternary alloy. A j The value of is equal to or less than the maximum solid solubility value for Mg, and is preferably 0.02 mol% or more and 1 mol% or less, more preferably 0.02 mol% or more and 0.5 mol% or less, and even more preferably 0.02 mol% or more and 0.3 mol% or less. j When the content is less than 0.02 mol%, the added solute element does not affect the mechanical properties or electrochemical properties and exists as an impurity element. When pure Mg is used as a Mg-based alloy material, the balance consists of Mg and unavoidable components such as iron, nickel, silicon, and copper, and it is usually desirable for the purity of Mg to be 99% or more.

[0021] The Al layer of the clad material is used as a current collector. The Al layer in this embodiment includes a pure Al layer and an Al alloy layer. That is, the Al layer may be pure Al or an Al alloy. The Al layer contains, for example, 99 mass% or more of Al. The Al layer may contain a small amount of impurities that are inevitably mixed in during production. The Al layer may contain an additive element. The additive element may be, for example, silicon (Si), iron (Fe), copper (Cu), manganese (Mn), magnesium (Mg), zinc (Zn), titanium (Ti), etc., and may also be Ag (silver), Ga (gallium), or Li (lithium). That is, the Al-based alloy is Al-B k mol%Y k (k=1, 2, …, m; m is a natural number equal to or greater than 1), and Y k=It is preferable that the alloy is composed of one of the following elements: Si, Fe, Cu, Mn, Mg, Zn, Ti, Ag, Ga, and Li. Here, if m is 1, it represents a binary alloy, and if it is 2, it represents a ternary alloy. B k The value of is 0.02 mol% or more and 1 mol% or less, and elements with a composition ratio of less than 0.02 mol% are considered to be unavoidable impurities. Of course, in consideration of the workability of the current collector and the bondability with the Mg-based alloy negative electrode material, an Al-based alloy to which an element that dissolves in Al is added may be used. Examples of Al alloys that can be used for the Al layer include alloy numbers "1085", "1070", "1050", "1N30", "1100", "3003", "3004", "8021", "8079", etc., as specified in "JIS H 4160: Aluminum and aluminum alloy foils". The Al layer may have a thickness of, for example, 5 μm or more and 50 μm or less. The Al layer may have a thickness of, for example, 10 μm or more and 20 μm or less.

[0022] The Mg layer made of Mg or Mg-based alloy and the Al layer made of Al or Al-based alloy are controlled by rolling and other stretching processes to control the internal microstructure, the thickness of the clad material, and the bonding between Al and Mg. Here, rolling is exemplified, but any method that can control the internal structure during solidification and adjust the thickness at the same time, such as the twin roll casting method, may be used. The layers may be two layers of Mg and Al, three layers of Mg, Al, and Mg, four layers of Mg, Al, Mg, and Al, or more. However, the order of layers must be Mg and Al. In the case of a clad material made of three or more layers, the Mg layer may be a Mg layer made of a different Mg or Mg-based alloy, as long as it satisfies the above-mentioned Mg layer made of Mg or Mg-based alloy. For example, a combination of pure Mg and an Mg-Mn alloy, or an Mg-Mn alloy and an Mg-Al alloy may be used. In addition, the Mg-based alloy and Al-based alloy used in the Mg layer and Al layer of the clad material may be a commercial Mg-based alloy known as AZ31 alloy or a commercial Al-based alloy known as 3000 series alloy. Known commercial Mg-based alloys include Mg-Al-Zn alloys (AZ91, AZ31, etc.), Mg-Al-Mn alloys (AM50, AM60, etc.), Mg-Zn-Zr alloys (ZK61, ZK60, etc.), and Mg-rare earth element alloys (EZ33, ZE41, WE43, EV31, etc.). In addition, among commercial Mg-based alloys, alloys such as AZ91, which are difficult to process into foils with a thickness of several hundred μm, are excluded because they are not suitable for use as negative electrode materials for Mg secondary batteries. In order to reduce weight, a commercial Mg-based alloy that can be processed into foils is desired for use as negative electrode materials for Mg secondary batteries.

[0023] The thickness of both the Mg layer and the Al layer created by these methods is preferably 0.5 mm or less. More preferably, it is 0.3 mm or less, and even more preferably, it is 0.15 mm or less. When used as a negative electrode material, the larger the surface area in contact with the electrolyte, the better the electrochemical efficiency, so if the thickness exceeds 0.5 mm, the efficiency will decrease. In addition, the weight of the secondary battery will increase, reducing the benefit of weight reduction.

[0024] Next, the characteristics of the internal microstructure of the clad material will be described. The average crystal grain size of each parent phase of the Al layer and Mg layer is preferably 5 μm or more, more preferably 10 μm or more, and even more preferably 20 μm or more. In metallurgy and electricity, in order to obtain excellent electrochemical properties, it is desirable to introduce a large amount of crystal grain boundaries to make the crystal grains finer, and the finer the crystal grain size, the better. However, in the case of foil materials with thin sample thickness, there are only a few to several tens of crystal grains in the cross-sectional (=thickness) direction, and in order to ensure cycle characteristics of 10 or more times, it is necessary to be concerned about local dissolution of the crystal grain boundaries. Here, cycle characteristics refer to the potential-current correlation obtained by cycle measurement, and are generally evaluated based on the number of cycles. In cyclic voltammetry (a method of measuring current response by scanning voltage at a constant speed and range), it is evaluated from the perspective of how many cycles the current value at a certain potential is maintained above a reference current value, and in constant current deposition dissolution, how many cycles the low overvoltage is maintained.

[0025] In addition, the standard deviation of the crystal grain size is preferably equal to or less than the average crystal grain size (100% or less), more preferably 75% or less, and even more preferably 50% or less. When coarse crystal grains and fine crystal grains are mixed, it is difficult for the charge / discharge cycle to occur uniformly over the entire surface of the negative electrode, and the heterogeneous fine structure region consisting of coarse or fine crystal grain sizes is likely to become a short circuit site for precipitation and dissolution, making it impossible to obtain the desired cycle characteristics and electrochemical characteristics. It is preferable to measure the crystal grain size using the section method (also called the cut method, see JIS H0501 and G0551) based on the JIS standard. However, when the crystal grain size is fine or the crystal grain boundary is unclear, it is difficult to use the section method, so it is acceptable to measure using a bright field image or an electron backscatter diffraction image obtained by a transmission electron microscope.

[0026] In addition, regarding the cross-sectional appearance of the clad material, it is desirable that there be no gaps at the boundary between the Al layer and the Mg layer. When the cross-section is observed using an optical microscope or a scanning electron microscope, the ratio of gaps is preferably less than 50%, more preferably less than 40%, and even more preferably less than 30%. If gaps of 50% or more are formed, a loss occurs in the charge / discharge characteristics, and the effect and function as a current collector are insufficient. In addition, the electrolyte may enter the gaps and become reaction sites for dissolution and precipitation, which may cause early short circuits.

[0027] In order to obtain the clad material, a stretching method capable of continuously introducing strain into the workpiece is desirable. Of course, as described above, it is not limited to rolling, and any method may be used as long as the internal structure is controlled during solidification and the thickness can be adjusted at the same time, as typified by the twin roll casting method. The temperature during stretching is preferably 300°C or higher, more preferably 350°C or higher, and even more preferably 400°C or higher. In addition, the strain imparted is preferably 0.05 or higher and less than 5, more preferably 0.075 or higher and less than 4, and even more preferably 0.1 or higher and less than 3, converted into true strain. When the processing temperature is less than 300°C, the grain size can be expected to be refined, but residual strain during processing remains in the Mg matrix. These are not preferable from the viewpoint of improving electrochemical properties, as they are likely to become short-circuit sites during charging and discharging. It is similar and not preferable to impart a true strain of 5 or more to the workpiece. On the other hand, when a true strain of less than 0.05 is applied, it becomes difficult for Al and Mg to bond well, resulting in a clad material with many gaps.

[0028] The electrochemical properties of Mg alloys are described below. In cycle measurements using a bipolar cell, the alloys preferably exhibit cycle characteristics of 5 times or more, more preferably 10 times or more, and even more preferably 15 times or more. If the cycle characteristics are less than 5 times, the alloy cannot be used as a negative electrode due to the problem of side reactions with the electrolyte. Here, cycle measurements refer to the relationship between potential and current obtained when a constant current / voltage or a current / voltage is applied for a certain period of time while repeatedly inverting the sign at a certain speed and within a certain range using a potentiogalvanostat.

[0029] Moreover, the overvoltage that can be obtained in the electrochemical deposition / dissolution test is preferably 50 mV or less, more preferably 30 mV or less, and even more preferably 20 mV or less. If the overvoltage is 50 mV or more, the loss of the battery voltage is large, and therefore the material cannot be used as a negative electrode. In the electrochemical deposition / dissolution test, the current value is preferably ±10 mAcm when the electrode potential is ±0.5 V. -2 More preferably, ±20mAcm -2 More preferably, ±25mAcm -2 The above values ​​are shown. Current value is ±10mAcm -2 If the resistance is less than 100%, the rate of the electric reaction is determined by the negative electrode, and the negative electrode cannot be used as a negative electrode. Here, the electrochemical deposition / dissolution test corresponds to the evaluation target in the cycle measurement. Therefore, the cycle measurement described in this specification means the cycle measurement of electrochemical deposition / dissolution, and the cycle characteristic described in this specification means the cycle characteristic of electrochemical deposition / dissolution. EXAMPLES

[0030] Pure Mg foil material (99.96 mass%) with a thickness of 50 μm and commercially available pure Al foil material (99 mass%) with a thickness of 50 μm were used. In addition, a rolling machine capable of heating the rolling rolls up to 300 °C was used for rolling processing. The Mg foil material and the Al foil material were overlapped and rolling processing was performed for two or more passes at a rolling roll temperature of 300 °C to create a clad material. The rolling processing was performed in air, and the reduction rate per pass was 10%. The created clad material was cut with a cross-sectional precision cutting machine, and examples of microstructural observations obtained by a scanning electron microscope and an electron beam backscatter diffraction method are shown in Figures 1 and 2. In Figure 1, a difference in contrast can be confirmed at the boundary between Mg and Al. There is no gap at the boundary, and Mg and Al are well bonded at the observation magnification level. In Figure 2, it can be seen that the average crystal grain sizes of Mg and Al are 15 μm and 10 μm. Furthermore, the contrast within each grain is homogeneous, suggesting the absence of residual strain within the grains.

[0031] To evaluate the electrochemical properties of Example 1, 0.5 mA cm -2 A constant current voltage test was performed at a current density of 1000 s. In this test, an electrolyte consisting of magnesium tetrakis(hexafluoroisopropoxy)borate and diethylene glycol dimethyl ether was used. The electrochemical characteristics were evaluated using a two-electrode cell, with a Mg alloy as the working electrode and a porous carbon material with a glass fiber filter as the counter electrode, on which 0.2 mL of the above electrolyte was dropped. As an example of a dissolution-precipitation reaction, the constant current voltage measurement profile is shown in Figure 3. In the constant current voltage measurement profile, the Mg deposition reaction occurs in the region where a negative voltage is applied, and the Mg dissolution reaction occurs in the region where a positive voltage is applied, with 0V vs. Mg as the reference. In both deposition and dissolution reactions, the deviation from 0V vs. Mg corresponds to the overvoltage. In one cycle of deposition-dissolution, the Coulombic efficiency can be calculated by taking the ratio of the current required for Mg deposition to the current required for Mg dissolution. Since the cycle characteristics are shown at a constant voltage, good dissolution and deposition reactions are occurring. On the other hand, a sudden voltage drop can be confirmed at 45 cycles, suggesting a short circuit. Note. All operations related to the electrochemical test were performed in a glove box under an argon atmosphere. EXAMPLES

[0032] A clad material was created in the same manner as in Example 1, except that a pure Mg foil material having a thickness of 50 μm and a pure Al foil material having a thickness of 50 μm were used and the Mg foil material, Al foil material, and Mg foil material were stacked in this order. FIG. 4 shows an example of a cross-sectional microstructure observation obtained by a scanning electron microscope. From the difference in contrast, it can be confirmed that the Al foil material is sandwiched between the Mg foil materials and that there is no gap at the boundary between Mg and Al. In addition, from the electron beam backscatter diffraction image shown in FIG. 5, the average crystal grain sizes of Mg and Al are 25 μm and 10 μm, and the microstructure is very similar to that of Example 1, except that the Al foil material is sandwiched between the Mg foil materials.

[0033] The electrochemical characteristics of Example 2 are shown in Figure 6. The electrochemical characteristics were evaluated under the same conditions as in Example 1, except that an electrolyte solution containing magnesium tetrakis(hexafluoroisopropoxy)aluminate and diethylene glycol dimethyl ether was used. It can be seen that the battery exhibits good charge / discharge characteristics and can be cycled 15 times or more.

[0034] 7 is a schematic diagram showing the schematic configuration of an Mg secondary battery in which the negative electrode material and current collector of the present invention are used. As shown in FIG. 7, the Mg secondary battery 1 includes a positive electrode 11, a negative electrode 12, an electrolyte 13, and a container 14.

[0035] In the positive electrode 11, a positive electrode active material (not shown) is held by a positive electrode collector (not shown). The positive electrode collector has a function of donating electrons to the positive electrode active material during discharge. As the material used as the positive electrode collector, nickel, iron, stainless steel, titanium, aluminum, etc. are preferably used because they have relatively excellent corrosion resistance and are inexpensive. As the material used as the positive electrode active material, there is no particular limitation as long as it can insert and remove Mg ions, but MgFeSiO4, MgMn2O4, V2O5, etc. are preferably used. As a specific configuration of the positive electrode 11, for example, a configuration in which V2O5 is coated on stainless steel can be mentioned.

[0036] For the negative electrode 12, the negative electrode material for Mg secondary batteries and the current collector of the present invention are used. The electrolyte 13 is held by a separator (not shown) and generates ionic conductivity between the positive electrode 11 and the negative electrode 12. The electrolyte 13 contains Mg ions. During discharge, the Mg ions cause a reduction reaction (for example, the reaction of formula (1) described below) at the positive electrode 11 and an oxidation reaction (for example, the reaction of formula (2) described below) at the negative electrode 12. During charge, the Mg ions cause an oxidation reaction (for example, the reaction of formula (3) described below) at the positive electrode 11 and a reduction reaction (for example, the reaction of formula (4) described below) at the negative electrode 12. These oxidation-reduction reactions enable the Mg secondary battery to be charged and discharged.

[0037] [C1] V2O5+Mg 2+ +2e- → MgV2O5… Formula (1) Mg → Mg 2+ +2e - … Formula (2) MgV2O5 → V2O5+Mg 2+ +2e - … Formula (3) Mg 2+ +2e - → Mg … Formula (4)

[0038] The positive electrode 11, the negative electrode 12, and the electrolyte 13 are sealed in a container 14. The material of the container 14 is not particularly limited as long as it does not leak the electrolyte and is corrosion-resistant, but a container formed by pressing a metal plate such as iron and having a plating layer of nickel or the like formed on the entire inner and outer surfaces for corrosion resistance is preferably used.

[0039] The above-described embodiment of the present invention merely describes one example of an Mg secondary battery, and should not be construed as limiting, and also includes technical matters that are self-evident in the technical field of Mg secondary batteries. [Industrial Applicability]

[0040] The negative electrode material and current collector for Mg secondary batteries of the present invention exhibit excellent electrochemical properties and can therefore be used as negative electrode materials and current collectors for Mg secondary batteries as well as Mg primary batteries. The negative electrode material for Mg secondary batteries and the current collector of the present invention can be used in Mg secondary batteries. [Explanation of symbols]

[0041] 1...Mg secondary battery 11...Positive electrode 12...Negative electrode 13...Electrolyte 14...Container

Claims

1. A clad material comprising an Mg layer made of Mg or an Mg-based alloy and an Al layer made of Al or an Al-based alloy, The Mg-based alloy is Mg-A j mol%X j (j=1, 2, ..., n; n is a natural number equal to or greater than 1), j X is for elements that are dissolved in Mg at 0.05 mol% or more. j = composed of any one of Al, Ag, Bi, Ca, Sn, Mn, Li, RE (rare earth), and Zn, and A j The value of is 0.02 mol% or more and 1 mol% or less, The Al-based alloy is Al-B k mol% Y k (k=1, 2, ..., m; m is a natural number equal to or greater than 1), and Y k = composed of any one of elements Si, Fe, Cu, Mn, Mg, Zn, Ti, Ag, Ga, and Li, and B k The value of is 0.02 mol% or more and 1 mol% or less, The Mg layer made of Mg or an Mg-based alloy is a negative electrode material, The Al layer made of Al or an Al-based alloy is an Al current collector. A negative electrode material and a current collector for Mg secondary batteries, characterized in that

2. The negative electrode material and current collector for Mg secondary batteries according to claim 1, The negative electrode material and current collector for Mg secondary batteries are characterized in that the thickness of the Mg layer is less than 100 μm, and the thickness of the Al layer is less than 100 μm.

3. The negative electrode material and current collector for Mg secondary batteries according to claim 1, the average crystal grain size of the Mg matrix of the Mg layer is 50 μm or less; The negative electrode material and current collector for Mg secondary batteries are characterized in that the average crystal grain size of the Al matrix of the Al layer is 50 μm or less.

4. The negative electrode material and current collector for Mg secondary batteries according to claim 1, A negative electrode material and current collector for Mg secondary batteries, characterized in that a gap of less than 50% exists at the boundary between Al and Mg in a cross section observed by an optical microscope or a scanning electron microscope.

5. The negative electrode material and current collector for Mg secondary batteries according to claim 1, A negative electrode material and a current collector for a magnesium secondary battery, characterized in that they exhibit cycle characteristics of 20 or more times in cycle measurements using a bipolar cell.

6. The negative electrode material and current collector for Mg secondary batteries according to claim 1, A negative electrode material and a current collector for Mg secondary batteries, characterized in that they exhibit an overvoltage characteristic of 30 mV or less in an electrochemical deposition-dissolution test of Mg metal.

7. The negative electrode material and current collector for Mg secondary batteries according to claim 1, In the electrochemical deposition and dissolution test of Mg metal, the current density was ±10 mA cm when the electrode potential was ±0.5 V. -2 The negative electrode material and current collector for Mg secondary batteries are characterized by exhibiting a current density of at least 1000 sq. m.

8. A method for producing the negative electrode material and current collector for Mg secondary batteries according to any one of claims 1 to 7, comprising the steps of: A method for producing a negative electrode material and current collector for Mg secondary batteries, comprising stacking an Mg layer made of Mg or an Mg-based alloy and an Al layer made of Al or an Al-based alloy, and applying plastic strain to the resulting material by wrought processing at a temperature of 300°C or higher so that the true strain is 0.05 or more and less than 5.

9. A method for producing a negative electrode material and a current collector for a Mg secondary battery according to claim 8, A method for producing a negative electrode material and a current collector for a Mg secondary battery, characterized in that the method for imparting plastic strain is any one of extrusion, forging, rolling, drawing, and twin-roll casting.

10. 8. A Mg secondary battery comprising the negative electrode material for Mg secondary batteries and the current collector according to claim 1, an electrolyte, and a positive electrode.